2016
DOI: 10.1016/j.canep.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection, H19 and LINC00152 expression in serum and risk of gastric cancer in a Chinese population

Abstract: Gastric cancer (GC) is a consequence of multifactorial and multistep processes. Helicobacter pylori (H. pylori) infection plays a crucial role in gastric carcinogenesis. Long non-coding RNAs (lncRNAs) have shown great potential as powerful cancer biomarkers. To investigate the possible roles of lncRNAs and H. pylori infection in GC development, we measured expression levels of three lncRNAs (H19, LINC00152, uc001lsz) in serum from a total of 285 Chinese participants using reverse transcription-quantitative pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 39 publications
2
48
0
Order By: Relevance
“…Our former study revealed that LINC00152 promoted tumor invasion and predicts poor prognosis in renal clear cell [8] and lung carcinomas [9] . Other studies have got similar findings in gastric cancer [10] and hepatic carcinoma [11] , suggesting that LINC00152 might serve as a powerful oncogenic lncRNA in somatic malignancies. Researchers have found that LINC00152 forms the loop feedback with FOXM1 to stimulate tumor growth [12] and might serve as the ceRNA (competing endogenous RNA) to regulate miRNAs to fulfil its biological functions [5,13,14] .…”
Section: Introductionsupporting
confidence: 59%
“…Our former study revealed that LINC00152 promoted tumor invasion and predicts poor prognosis in renal clear cell [8] and lung carcinomas [9] . Other studies have got similar findings in gastric cancer [10] and hepatic carcinoma [11] , suggesting that LINC00152 might serve as a powerful oncogenic lncRNA in somatic malignancies. Researchers have found that LINC00152 forms the loop feedback with FOXM1 to stimulate tumor growth [12] and might serve as the ceRNA (competing endogenous RNA) to regulate miRNAs to fulfil its biological functions [5,13,14] .…”
Section: Introductionsupporting
confidence: 59%
“…LINC00152 was overexpressed in several cancers, including esophageal squamous cell carcinoma, colorectal cancer, gastric cancer, and hepatocellular carcinoma . Increased LINC00152 levels might be potential biomarkers for predicting the poor progress of these cancers . Mechanistically, LINC00152 overexpression dramatically promoted gallbladder cancer growth by regulating the phosphatidylinositol 3‐kinase (PI3K)/AKT signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…25 Increased LINC00152 levels might be potential biomarkers for predicting the poor progress of these cancers. [26][27][28][29][30][31] Mechanistically, LINC00152 overexpression dramatically promoted gallbladder cancer growth by regulating the phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathway. 9 Chen et al revealed that LINC00152 was dramatically upregulated in gastric cancer and was positively correlated with tumor invasion, TNM stage, and poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, linc00152 is upregulated in various cancers including gastric cancer [145,147,352,353], lung cancer [144], gall bladder cancer [148,149], renal cell carcinoma [354], and pancreatic cancer [355], whilst its expression has been found to be downregulated in colorectal cancer [356]. linc00152 can act via a ceRNA network for miR-139-5p in gastric cancer [143], and acts as a competing endogenous RNA to modulate the expression of miR-193a-3p in colon cancer [151], and acts as a ceRNA for miR-138 in gallbladder cancer [148].…”
Section: Lncrnas and Emt: The Main Playersmentioning
confidence: 99%